Porcine Viruses - Simon Graham (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Pig production is the fastest growing segment of the global livestock sector. Intensification of pig production has resulted in significant changes to traditional pig husbandry practices. Combined with urbanization and ease of travel and transport, these changes have led to an environment conducive to increased emergence and spread of viral diseases. The past decade alone has seen the global emergence and re-emergence of porcine viruses with devastating consequences: For example, in 2006, highly pathogenic porcine reproductive and respiratory syndrome viruses (PRRSV) spread rapidly across Southeast Asia killing millions of animals; since its introduction into the Caucasus in 2007, the African swine fever virus has steadily spread to Eastern Europe; and in 2013-14, over 8 million pigs died when virulent porcine epidemic diarrhea virus (PEDV) swept North America. In this special issue we will explore our understanding of porcine viruses and how this may be exploited to improve the control of these pathogens of economic and agricultural significance.